Penerapan Konseling Behavioral Dengan Teknik Penguatan Positif untuk Meningkatkan Minat Belajar Siswa SMA - Pradnyanica Luh Ade; Giri Putu Agus Semara Putra (Jurnal Bimbingan dan Konseling Indonesia, 2023)
The goal to be achieved in this research is to increase the learning interest of class X.2 students of SMA Dwijendra Denpasar for the 2022/2023 academic year through the application of behavioral counseling with positive reinforcement techniques. The research subjects were class X.2 students who had high deviant behavior totaling 5 students consisting of 3 male students and 2 female students. Based on the results of the data and discussion of the results - the results of the study can be concluded (1) there is an increase in student interest in learning individually and in groups. (2) the score of students' interest in learning before the group action was 221 and the average was 44.2 after being given the action in cycle I became 303 and the average was 60.6 with the percentage increase as a group of 176.5% with an average of 35.3 %. In cycle II, the score increased again to 381 and an average of 76.2 with an increase in group percentage of 193.2% with an average of 38.64%. Thus the results of this study can be concluded that the application of behavioral counseling with positive reinforcement techniques can increase student interest in class X.2 SMA Dwijendra Denpasar, academic year 2022/2023.